Mykola Makarenko and Mariupol Neolithic Burial Ground The tragic fates of the archaeologist and the site - Mykhailova, Nataliia (Archaeologia Lituana, 2024)
Mariupol Neolithic burial site, unique by its exclusive rich and diversiform inventory, was excavated by Ukrainian archaeologist and art critic Mykola Makarenko in 1930. The author of the excavations was executed by Soviet punitive authorities. The top-level and highly informative publication of the materials on the cemetery, made in 1933, was confiscated. Part of the burial inventory was taken to Russia. Anthropological materials were destroyed during World War II.The tragedy of Mariupol Cemetery continued in 2022. This was the year which became the tragedy in the history of Ukraine and inherently influenced the history of Europe. The Ukrainian people, the Ukrainian nature, and the Ukrainian culture suffered irretrievable losses. So did Ukrainian archaeology.Hundreds of archaeological sites in the war zone, in the zone of occupation and in the annexed territories were completely destroyed or irreparably damaged. Among them, there were the scant surviving artifacts from Mariupol Cemetery.This article is devoted to the history of excavations of Mariupol Burial Complex and the tragic fate of the collection of artifacts.
Keywords: Neolithic; Mariupol Cemetery; burials; Mariupol-type burial grounds; cultural heritage